2018
DOI: 10.1111/jnu.12429
|View full text |Cite
|
Sign up to set email alerts
|

The Woodhull Study Revisited: Nurses’ Representation in Health News Media 20 Years Later

Abstract: PurposeTo determine if nurses are represented in health news stories more frequently today than 20 years ago when Sigma Theta Tau International Nursing Honorary Society published The Woodhull Study on Nursing and the Media, which found that nurses were cited as sources in only 4% of the stories.DesignContent analysis of health news stories for the month of September 2017 in the same publications used in the original Woodhull study.MethodsSearches with Nexis and Webhose identified 2,243 articles related to heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 8 publications
1
58
0
1
Order By: Relevance
“…Despite nurses' major contribution to the economic and social development of a country, they are usually missing from the media coverage of the health sector and, consequently, kept away from public discussion . Mason et al analyzed 537 articles from 13 American health publications and concluded that nurses were identified as sources of only 2% of quotes in the articles, were mentioned in 13% of stories, and were identified in 4% of images in the articles. The authors concluded that 20 years after the initial study, which found the profession was almost invisible, there were no significant changes in the profession's representation in the media .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite nurses' major contribution to the economic and social development of a country, they are usually missing from the media coverage of the health sector and, consequently, kept away from public discussion . Mason et al analyzed 537 articles from 13 American health publications and concluded that nurses were identified as sources of only 2% of quotes in the articles, were mentioned in 13% of stories, and were identified in 4% of images in the articles. The authors concluded that 20 years after the initial study, which found the profession was almost invisible, there were no significant changes in the profession's representation in the media .…”
Section: Introductionmentioning
confidence: 99%
“…Mason et al analyzed 537 articles from 13 American health publications and concluded that nurses were identified as sources of only 2% of quotes in the articles, were mentioned in 13% of stories, and were identified in 4% of images in the articles. The authors concluded that 20 years after the initial study, which found the profession was almost invisible, there were no significant changes in the profession's representation in the media . Media invisibility and unfavorable representations can negatively influence the choice of nursing as a profession, contribute to resource allocation, and violence against nurses, leading to recruitment and retention problems, with an impact on safe staffing, and professional dissatisfaction .…”
Section: Introductionmentioning
confidence: 99%
“…Yes, nurses are viewed as being honest and ethical. But, according to a study that examined how the representation of nurses in the media has changed over the past twenty years, nurses are still largely invisible, and are generally not acknowledged for their expertise or central role in health care (Mason et al, 2018). Such undervaluing of nursing leads to the persistence of longstanding stereotypes, and thus nursing may continue to receive inadequate resources for education, research, practice, and residency programs (Summer & Broome, 2019).…”
mentioning
confidence: 99%
“…In the same study performed again in 2017, little had changed, with only 2 percent of quotes coming from nurses, 4 percent of images including a nurse, and 13 percent of articles referring to nurses . The authors of the 2017 study also interviewed health journalists to better understand this underrepresentation.…”
mentioning
confidence: 99%
“…The authors of the 2017 study also interviewed health journalists to better understand this underrepresentation. These journalists indicated that they did not completely understand the varying roles and work of nurses and often did not know how to find them for interviews in a limited amount of time . Other identified barriers included that health care organization communications personnel typically do not recommend nurses as sources and that nurses may not be proactive about engaging with the media …”
mentioning
confidence: 99%